Perancangan Informasi Melalui Media Collectible Cards Hewan Purba Zaman Mesozoikum - Wiguna, Mochamad Gunawan; Tarmawan, Irwan (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2022)
The Mesozoic era is one of the eras where the earth was occupied by various kinds of ancient animals. In the Mesozoic era there were three epochs, namely the Triassic, Jurassic, and closed with the Cretaceous period where ancient animals at this time began to become extinct. Currently, public knowledge about the Mesozoic era is still lacking and dominantly still identifying ancient animals in the Mesozoic era, only dinosaurs, especially T-Rex. In fact, there were many other types of animals living in this era including various types of dinosaurs, mammals, marine animals, or birds. The purpose of this design is to provide information and general knowledge that in the Mesozoic era there were various types of ancient animals that were diverse and unique which were the ancestors of most of today's animals that have evolved. The media used in this design is using different media than the general media currently used, namely by using collectible cards media which are presented with more specific information. The media in this design is also distributed through an official institution, namely the Bandung Geology museum so that the information presented can reach a wider audience and the public can more easily receive the information presented. This design is expected to provide a solution for people who have difficulty in identifying ancient animals in the Mesozoic era.